Developing skills for youth in the 21st century: The role of elite International Baccalaureate Diploma Programme schools in China - Wright, Ewan; Lee, Moosung (International review of education, 2014)
There is a growing body of research suggesting that schools need to respond to changing social and economic dynamics by prioritising "21st-century skills". Proponents of this view, who have been termed "the 21st century skills movement", have called for greater emphasis on cognitive and non-cognitive skills development, alongside the learning of subject content and technical skills. This paper explores the potential of International Baccalaureate Diploma Programme (IBDP) schools to respond to this mandate in China, one of the fastest-growing markets for International Baccalaureate® (IB) schools globally. The authors' research team undertook a multi-site case study of five elite IBDP schools in China. Their findings revealed confidence among interviewees that the IB educational philosophy was conducive to 21st-century skills development, especially through the provision of the three IBDP "Core Requirements", which are Creativity, Action, Service (CAS), Extended Essay (EE) and Theory of Knowledge (TOK). Despite this confidence, concerns remain about the implementation of the IB educational philosophy in the context of IBDP schools in China. Un corpus croissant d'études propose que les établissements scolaires réagissent à la nouvelle dynamique sociale et économique en accordant la priorité aux « compétences pour le XXIe siècle ». Les adeptes de ce point de vue, désignés par le « mouvement des compétences pour le XXIe siècle », appellent à valoriser l'acquisition des compétences cognitives et non cognitives, parallèlement à l'apprentissage du contenu des matières et des compétences techniques. Cet article explore le potentiel des écoles du Programme du diplôme du Baccalauréat international (IB) de remplir cette mission en Chine, l'un des marchés à plus forte croissance au monde pour les écoles de l'IB. L'équipe de chercheurs des auteurs a entrepris une étude de cas multi-sites dans cinq écoles chinoises de l'IB. Leurs résultats établissent que les personnes interrogées estiment la philosophie pédagogique de l'IB favorable à l'acquisition des compétences pour le XXIe siècle, notamment à travers les trois « composantes obligatoires » de l'IB : le mémoire, la théorie de la connaissance et le programme créativité, action, service (CAS). Malgré ces réponses positives, des doutes ont été émis quant à l'application de la philosophie pédagogique de l'IB dans le contexte des écoles concernées en Chine.